Association Between Benign Ovarian Tumors and Ovarian Cancer Risk: A Meta-Analysis of Ten Epidemiological Studies - Guo, Jiao; Feng, Haoshen; Gu, Xi (Frontiers in Oncology, 2022)
Background Epidemiological evidence on the relationship between benign ovarian tumors and ovarian cancer risk has been controversial; therefore, this systematic review and meta-analysis evaluated this association. Methods The PubMed and Web of Knowledge databases were searched for eligible studies published up to April 30, 2020. The study-specific risk estimates were pooled using a random-effects model. Results Ten articles (two cohorts, seven case-control studies, and one pooled analysis of eight case-control studies) with 10331 ovarian cancer patients were included. Benign ovarian tumors were associated with an increased risk of ovarian cancer (pooled relative risk [RR]=1.39, 95% confidence interval [CI]: 1.01–1.90), with high heterogeneity among studies. The pooled RR was 2.02 (95%CI: 1.32–3.11) for two cohort studies, which was higher than the pooled result of eight case-control studies (pooled RR: 1.15; 95%CI: 0.92–1.44). When stratifying by histological type, the pooled RRs were 1.53 (95% CI: 0.37–6.29) and 3.62 (95%CI: 0.81–16.20) for serous and mucinous tumors, respectively. The pooled RRs were 1.61 (95%CI: 0.65–3.95) and 1.54 (95%CI: 1.29–1.84) for the associations of ovarian cyst with invasive and borderline cancers, respectively. Conclusions Benign ovarian tumors were associated with an increased risk of ovarian cancer. Due to the high heterogeneity among the studies and the risks of bias, more studies are warranted to confirm these findings.